Case report: An elderly woman with recurrent syncope after pacemaker implantation - Sun, Yanxiang; Feng, Li; Huang, Xuansheng; Hu, Bing; Yuan, Yong (Frontiers in Cardiovascular Medicine, 2023)
Syncope due to atrioventricular block may occur as a result of a cardiac vasodepressor reflex. This article reports a case of recurrent syncope in an 80-year-old woman with high-grade atrioventricular block documented by electrocardiographic monitoring after pacemaker implantation. Pacemaker testing revealed stable impedance and sensing, but obvious increasing ventricular capture threshold at outputs. What makes this case unusual is that the patient’s principal diagnosis was noncardiac. Combined with high D-dimer, hypoxemia and computerized tomography scan of the pulmonary artery, the pulmonary embolism (PE) was finally confirmed. The ventricular capture threshold gradually dropped to the normal range and the syncope disappeared after anticoagulant therapy for one month. This is the first report of electrophysiology phenomenon by pacemaker testing in this patient with syncope due to PE.